Associations between dyadic adjustment and psychological symptoms: A preliminary study for assessing therapeutic change for couples - Araç, Hazel Irmak (İstanbul Bilgi Üniversitesi, 2019)
[Abstract Not Available]
Çift uyumu ve psikolojik semptomlar arasındaki ilişki: Çift terapisinin çiftlerdeki etkisine dair bir ön çalışma